Greening Public Policy: The Effects of Environmentally Friendly Regulations, Public Support, Sustainability Orientation on Green Governance - Erna, Erna; Mutaqin, Zenal (International Journal of Energy Economics and Policy, 2023)
Developments in the public sector continue to increase with the emergence of various types of services that experience changes and demands from the public to public sector reform to pay more attention to green governance and orientation in various public policies. This is because climate change and environmental degradation are increasingly becoming a global concern and are increasingly showing their negative impacts. The public is increasingly aware that environmental protection and sustainability are very important. Therefore, the use of renewable energy is important to implement in supporting green governance. Green policies were largely adopted as the impact of climate change worsening. In public sector, the policies were used as a benchmark for environmentally friendly policies. The purpose of this research is to identify and analyze the effect of regulations related to the environment, public support, and sustainability orientation towards green governance by implementing renewable energy which is mediated by green public procurement. The research was conducted using a quantitative approach. A total of 214 respondents from environmental agencies’ employees used a simple random sampling technique. The data analysis technique used is Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of this study indicate that regulations related to the environment, public support, and sustainability orientation have a positive effect on green public procurement and green governance. Furthermore, green public procurement is able to mediate the influence of environmental regulations, public support, and green perceptions on green governance.